2020
DOI: 10.1002/slct.201904170
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Antioxidative Activity of Apigenin by B12N12 Nanocluster: Antioxidative Mechanism Analysis

Abstract: Adsorption and antiradical activity of apigenin on the surface of B12N12 nanocluster has been investigated by using density functional theory (DFT) within B3PW91‐D and M06‐2X−D methods. Adsorption values and analysis of topologies showed that the molecule has chemisorbed to the nanocluster surface and induces significant changes in electronic properties of the fullerene. Antioxidative activities of the APG and APG/B12N12 complex have been investigated using the M06‐2X−D level of theory based on the hydrogen at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
2
3
0
Order By: Relevance
“…The optimized structures of TMZ, B 12 N 12 and Al 12 N 12 are depicted in figure 1, alongside the distribution of the FMOs of TMZ. The geometric parameters obtained herein from the optimized structures of pure B 12 N 12 (B-N bond lengths and angles) and Al 12 N 12 (Al-N bond lengths and angles) are in perfect agreement with those reported in the literature [3537]. The structure obtained from the relaxation of TMZ is displayed in figure 1, along with the interatomic distances in gas phase.…”
Section: Resultssupporting
confidence: 85%
“…The optimized structures of TMZ, B 12 N 12 and Al 12 N 12 are depicted in figure 1, alongside the distribution of the FMOs of TMZ. The geometric parameters obtained herein from the optimized structures of pure B 12 N 12 (B-N bond lengths and angles) and Al 12 N 12 (Al-N bond lengths and angles) are in perfect agreement with those reported in the literature [3537]. The structure obtained from the relaxation of TMZ is displayed in figure 1, along with the interatomic distances in gas phase.…”
Section: Resultssupporting
confidence: 85%
“…Little increments in the BDE values of Jug and Jug OH can be observed when they are adsorbed at the external surface of the B 12 N 12 nanocage. A similar observation has been made by Khalili and coworkers in their evaluation of the effect of adsorption of apigenin by the B 12 N 12 nanocluster on the antioxidative activity of the former [19]. The BDFE values presented in Table 5 follow the same trend with BDEs and are found to be smaller.…”
Section: Analysis Of the Aoa Descriptorssupporting
confidence: 84%
“…F I G U R E 1 Gas phase relaxed geometries of B 12 N 12 , Jug, Jug OH, A, B, C, and A OH obtained at DFT/M05-2X(D3)/6-311+G(d,p) level of theory Indeed, Minnesota set functionals have been successfully applied to simulate the structural and energetic parameters of cage nanostructures [9,10,19,37,38] . In addition, the M05-2X hybrid is suitable in describing weak interactions in molecular systems.…”
Section: Computational Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Soltani et al confirmed that B 12 N 12 was more preferable than B 16 N 16 in the drug delivery process of a 5-aminolevulinic acid (5-AVA) drug [ 12 ]. By an arc-melting method, B 12 N 12 was first synthesized with a band gap of 5.1 eV [ 13 , 14 ]. Afterward, B 12 N 12 was extensively investigated to serve as a nanocarrier of diverse anti-cancer drugs such as Isoniazid [ 6 ], Amphetamine [ 15 ], Lomustine [ 16 ], etc.…”
Section: Introductionmentioning
confidence: 99%